Alternative service delivery for senior citizen care services in Malaysia - Mohd Alwi, Norhayati; Alias, Intan Aidura; Mat Yassin, Fatimah (Centre for Research on Islamic Banking & Finance and Business, 2021)
Under the New Public Management (NPM), Alternative Service Delivery (ASD) provides opportunities to third parties to be involved in the provision of services. This research aims to explore the use of ASD business model under the NPM for senior citizen care services. Specifically, the research attempts to provide insights on the level of involvement of third parties and the challenges that they faced including financial sustainability when providing care services for senior citizens. To achieve the objectives, data on the financial sustainability of 16 non-governmental organisations (NGOs) that provide senior citizen residential care services around Peninsular Malaysia were collected. Specifically, survey questionnaires were given to assess the NGOs’ financial sustainability. The top management of the NGOs were also interviewed to obtain further insights. Analysis indicated that the NGOs relied on several financial resources to manage the care services and most of the centres have very limited amenities and a small number of staff. The findings may provide guides on the proposed business model and strategies for ASD implementation in senior citizen care services.